ANALISIS KINERJA APARAT SIPIL NEGARA (ASN) DI DINAS PENDIDIKAN DAN KEBUDAYAAN DAERAH PROVINSI SULAWESI TENGAH - Rindah, Rindah (Katalogis, 2017)
This study was conducted to analyze the performance of state civil apparatus at Central Sulawesi Department of Eduvation and Culture. This study used Qualitative research type, where according to moleong (2007:6) is the research that provides an overview of a causal problem relationship that is measured at one time or periode, so that it could describe the performance of Central Sulawesi Departement of Education and cultural’s employess. Data was collected by means of interviews, observations and documentations. The result shows that quality, quantity, timeliness, cost effectiveness, need for supervision, interpersonal impact an superior’s support were the important factors in improving the performance of central Sulawesi Department of Education and Culture’s employee.